2014
DOI: 10.2337/db13-1651
|View full text |Cite
|
Sign up to set email alerts
|

Limited Acute Influences of Electrical Baroreceptor Activation on Insulin Sensitivity and Glucose Delivery: A Randomized, Double-Blind, Crossover Clinical Study

Abstract: Arterial baroreflexes may regulate resistance vessels supplying glucose to skeletal muscle by modulating efferent sympathetic nervous system activity. We hypothesized that selective manipulation of baroreflex activity through electrical carotid sinus stimulation influences insulin sensitivity by changing muscular glucose delivery. We enrolled 16 hypertensive patients who responded to treatment with an electrical carotid sinus stimulator. Patients were submitted to a frequently sampled intravenous glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…110 However, in a randomized, double-blind, crossover study of 16 patients with hypertension who were defined as BP responders to baroreflex activation therapy, acute baroreceptor stimulation had no discernible effect on insulin sensitivity. 111 Furthermore, in patients with chronic kidney disease, muscle SNA is increased in proportion to the degree of renal impairment. 59,110,112,113 Sympathetic overactivity, therefore, constitutes a putative therapeutic target to slow progression of chronic kidney disease and its cardiovascular complications.…”
Section: Current and Potential Indicationsmentioning
confidence: 99%
“…110 However, in a randomized, double-blind, crossover study of 16 patients with hypertension who were defined as BP responders to baroreflex activation therapy, acute baroreceptor stimulation had no discernible effect on insulin sensitivity. 111 Furthermore, in patients with chronic kidney disease, muscle SNA is increased in proportion to the degree of renal impairment. 59,110,112,113 Sympathetic overactivity, therefore, constitutes a putative therapeutic target to slow progression of chronic kidney disease and its cardiovascular complications.…”
Section: Current and Potential Indicationsmentioning
confidence: 99%
“…In humans, there is an inverse relationship between insulin sensitivity and whole body NE spillover in obese individuals, and MSNA is higher in those with insulin resistance compared to those who are insulin sensitive 10 . Not all studies, however, have found that sympathetic activity is associated with decreased insulin sensitivity 11, 12 . Furthermore, a direct causal link between the sympathetic nervous system and insulin sensitivity has not been established in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of these findings in properly controlled clinical trials is mandatory [37‱]. In an acute study by our group, electrical carotid sinus stimulation did not improve glucose metabolism assessed by frequently sampled intravenous glucose tolerance testing [38].…”
Section: Evidence For Organ Protection?mentioning
confidence: 69%